The Model of Finance Contour Integration into Organization Strategy - V. V. Maslennikov; Yu. V. Lyandau; I. A. Kalinina; E. V. Popova (Вестник Российского экономического университета имени Г. В. Плеханова)
Finance management is an integral part of the general system of organization management, it is considered as an object and means of strategic management, as a sum total of methods and ways, which could provide enhancement of finance sustainability and obtaining maximum profits from functioning in the interests of its owners. However, finance management as a part of organization management requires formalization in view of choosing and applying finance tools of strategic planning, where strategy of organization development is seen as goal setting that can ensure the leading positions on market. The article analyzes financial development and organization standing on the basis of finance monitoring conducted by the service of finance control. According to the authors, it could resolve a number of problems, such as development and use of methodology of assessing business value with regard to rising profit, providing full finance accounting to executives and business owners.